2022
DOI: 10.1038/s41598-022-18604-y
|View full text |Cite
|
Sign up to set email alerts
|

Electrical resistivity of polycrystalline graphene: effect of grain-boundary-induced strain fields

Abstract: We have revealed the decisive role of grain-boundary-induced strain fields in electron scattering in polycrystalline graphene. To this end, we have formulated the model based on Boltzmann transport theory which properly takes into account the microscopic structure of grain boundaries (GB) as a repeated sequence of heptagon–pentagon pairs. We show that at naturally low GB charges the strain field scattering dominates and leads to physically reasonable and, what is important, experimentally observable values of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Ref. 85 calculated GB resistance as a function of angle, finding it to be significantly smaller for small-angle misalignment, while Ref. 86 suggested that non-straight GBs have substantially less misorientation angle dependence of the GB resistance at higher angles, while still decreasing rapidly ≤ 8°.…”
Section: Resultsmentioning
confidence: 99%
“…Ref. 85 calculated GB resistance as a function of angle, finding it to be significantly smaller for small-angle misalignment, while Ref. 86 suggested that non-straight GBs have substantially less misorientation angle dependence of the GB resistance at higher angles, while still decreasing rapidly ≤ 8°.…”
Section: Resultsmentioning
confidence: 99%
“…Using a Boltzmann transport equation (BTE) approach is also another approach that could be taken to model the impact of GBs [42], but it does so by considering a distribution of GBs, while in this work the atomic structure and the electronic and conductive properties which arise from this structure is considered using DFT-non-equilibrium Greens functions (NEGF). BTE is also usually assumes incoherent charge carriers scattering from a density of defects within linear response.…”
Section: Discussionmentioning
confidence: 99%
“…the long-ranged effects of variations in strain due to the presence of GBs [42] or substrate. On the scale of our computational cells we believe that the strain and substrate effects are secondary to the main scattering effects provided by the GB itself.…”
Section: Geometry Relaxation Using Dft (3d)mentioning
confidence: 99%